"Violence and the Sacred": sacrifice, scapegoating and social conflict in Alfonso Reyes' Ifigenia cruel. (24th October 2016) - Shaughnessy, Lorna
Abstract: This article presents a reading of Alfonso Reyes' Ifigenia cruel informed by René Girard's theories of 'mimetic violence' and 'the scapegoating effect'. It seeks to foster interest in the complex relationship between the play and the Mexican political context at the time of its composition, by examining both in the light of Girard's understanding of social conflict and sacrifice. It identifies Reyes' use of sacrificial metaphor as part of a complex continuum that includes Euripides' Iphigenia in Aulis and Iphigenia in Tauris . Where older versions of the myth end with deliverance for the heroine, however, Reyes' text ends on a darker note. It is argued that Ifigenia cruel should not be read as a text that promotes the triumph of peace through the heroine's rejection of her past, but rather as one where self-sacrifice and the shadow of scapegoating, as understood by Girard, reflect a Mexico racked by continuing violence.